Illness and enlightenment: exploring Tibetan perspectives on madness in text and everyday life - Deane, Susannah (Berghahn Books, 2025)
Tibetan understandings of nyoné — ‘madness’— encompass a broad range of concepts. Perspectives on the causation and treatment of madness as an illness are informed by Tantric and medical understandings of mind-body structure and (dys)functioning, as well as people’s relationships with non-human entities. In addition, ‘madness’ may be seen as a sign of enlightenment in the case of some Tantric practitioners. Based on ethnographic fieldwork in the Tibetan region of Amdo in northwest China, as well as examination of Tibetan medical and religious texts, Illness and Enlightenment explores the multi-faceted concept of nyoné through key Tibetan concepts of wind, heart, and mind, as well as human-spirit relationships